Peran Filsafat Ilmu dalam Psikologi Pendidikan - Wahyuni, Sri (Sultan Idris Journal of Psychology and Education, 2024)
This article examines the fundamental contribution of philosophy of science in the development of educational psychology in Indonesia through a systematic literature review approach. The background of this study is based on the fact that psychology was originally part of philosophy, and until now philosophy of science remains an important foundation for the development of culturally relevant educational theories and practices. The purpose of this study is to analyze the contribution, influence, and integration of philosophy of science in the formation of a contextual framework for thinking in Indonesian educational psychology. The method used is a systematic literature review from academic sources such as Hanurawan (2022), Gutek (2004), Freire (1970), Dewantara (2009), and Santrock & Yussen (2009), which discuss the pillars of philosophy of science, namely ontology, epistemology, and axiology in the context of education. The results of the study show that philosophy of science plays an important role in forming theories that are in accordance with local cultural values, aligning education with the diversity of Indonesian culture, and strengthening critical reflection and integration of character education. Philosophy of science also encourages a holistic approach to education that considers social, moral, and spiritual dimensions. Integration of Western psychological theory with local wisdom through culture-based learning models and culturally sensitive evaluations is an important strategy in developing an inclusive and relevant education system. Thus, philosophical understanding provides a contextual direction and methodological framework for the development of educational psychology in Indonesia that is able to respond to contemporary social, cultural, and pedagogical challenges.